Trabalho com projetos na formação inicial de professores de matemática na perspectiva da educação inclusiva - Cintra, Vanessa de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study is inserted in the field of Mathematics Education, specifically within the Mathematics teachers education in the perspective of Inclusive Education. Its aim is to analyze the engagement of Mathematics majors while developing and implementing investigative projects related to the theme Inclusion. The research question was the following: What comprehensions can be produced from the work with projects addressing the Inclusive Education in the pre-service Mathematics teachers' education? The research was based on a qualitative approach and the data was collected in the context of two courses, in different and subsequent moments, both of them part of the Teaching degree in Mathematics curriculum, in a public university in the state of Minas Gerais, Brazil. In these courses, we had project work, in which students, divided into small groups, studied, developed and implemented investigative projects. Therefore, the analyzed data consist of expressions of the undergraduate students, both individually and in group, and the researcher's field notes. To guide the data analysis, we had, as a base, some procedures of Content Analysis, from the perspective of the theory of project approach, regarding Inclusive Education and Teachers Training. The study made it possible for the Mathematics majors to have autonomy on the construction of their own knowledge, participating actively in the developed activities, creating a reflective and investigative attitude. The students explored and questioned their previous knowledge, ideologies, interpretations, and practices, challenging assumptions and proposing problems. The investigative projects that were developed promoted learning about the theme inclusion and also an understanding of aspects related to the teaching and learning of Mathematics for students with Special Educational Needs, developing a critical attitude regarding inclusive education

Esta pesquisa está inserida no campo da Educação Matemática, mais especificamente no âmbito da formação de professores de Matemática na perspectiva da Educação Inclusiva. Seu objetivo consiste em analisar o envolvimento de alunos de um curso de Licenciatura em Matemática ao elaborar e executar projetos de investigação relativos ao tema Inclusão. A pergunta que direcionou a pesquisa foi Que compreensões podem ser produzidas a partir do trabalho com projetos abordando a Educação Inclusiva na formação inicial de professores de Matemática? Fundamentada na abordagem qualitativa, a produção dos dados desenvolveu-se no contexto de duas disciplinas, em momentos diferentes e subsequentes, do curso de Licenciatura em Matemática, em uma Universidade Pública do Estado de Minas Gerais. Nessas disciplinas, foi desenvolvido um trabalho segundo a perspectiva da metodologia de trabalho com projetos, em que os alunos, divididos em grupos, estudaram, elaboraram e desenvolveram projetos de investigação. Assim, os dados analisados são constituídos por manifestações dos licenciandos, tanto individuais quanto em grupo e o diário de campo da professora pesquisadora. Para direcionar a análise dos dados, teve-se por base alguns conceitos da Análise de Conteúdo, sob a ótica da teoria sobre metodologia de trabalho com projetos, na perspectiva da Educação Inclusiva e Formação de Professores. O estudo possibilitou que os licenciandos tivessem autonomia na construção do seu próprio conhecimento, participando de forma ativa nas atividades que foram desenvolvidas, gerando uma postura reflexiva e investigativa. Para isso, exploraram e questionaram seus conhecimentos prévios, ideologias, interpretações, práticas, desafiando suposições e propondo problemas. Os projetos de investigação desenvolvidos promoveram uma aprendizagem sobre o tema inclusão e também a compreensão de aspectos relacionados ao ensino e à aprendizagem da...
Keywords: Teachers, Training of; Professores - Formação; Educação inclusiva; Educação especial; Inclusão na educação; Projetos - Elaboração; Crianças deficientes - Educação; Matemática - Estudo e ensino